1984
DOI: 10.1210/jcem-58-1-87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Testosterone on Somatomedin-C Concentrations in Prepubertal Boys*

Abstract: To investigate the role of testosterone (T) in the pubertal elevation of somatomedin-C (SmC), six prepubertal GH-deficient boys were each given 7-day courses of GH alone (0.05 U/kg X day, im), T alone (T propionate; 25 mg/day, im), and a combination of GH and T at the same dosages. Plasma SmC levels were determined on samples drawn at the start and finish of each period, and each course was separated by a 7-day period. SmC was also measured before and after a course of T propionate (25 mg/day, im) in four GH-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
2

Year Published

1986
1986
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(49 citation statements)
references
References 21 publications
2
45
2
Order By: Relevance
“…Wilson reported that gonadal steroids including testosterone have increased IGF-1 levels in the prepubertal female rhesus macaque [14]. It has also been reported that testosterone stimulates IGF-1 production in prepubertal boys capable of secreting GH [27]. These results clearly indicate that testosterone controls plasma IGF-1 levels in adolescent males.…”
Section: Figmentioning
confidence: 80%
“…Wilson reported that gonadal steroids including testosterone have increased IGF-1 levels in the prepubertal female rhesus macaque [14]. It has also been reported that testosterone stimulates IGF-1 production in prepubertal boys capable of secreting GH [27]. These results clearly indicate that testosterone controls plasma IGF-1 levels in adolescent males.…”
Section: Figmentioning
confidence: 80%
“…Moreover, the induction of puberty by exogenous androgen or GnRH induces high-amplitude GH secretion (Blizzard et al 1989, Foster et al 1989. Very small doses of testosterone, similar to those observed in early puberty, are sufficient to increase GH pulse amplitude (Guistina et al 1997), GHRH-induced GH release (Mauras et al 1989a) and circulating IGF-I levels (Parker et al 1984). The increase in IGF-I is due to GH rather than direct effects of testosterone, since IGF-I is increased by co-administration of GH and testosterone but not by testosterone alone in GH-deficient boys (Parker et al 1984).…”
Section: Puberty: Humansmentioning
confidence: 94%
“…Very small doses of testosterone, similar to those observed in early puberty, are sufficient to increase GH pulse amplitude (Guistina et al 1997), GHRH-induced GH release (Mauras et al 1989a) and circulating IGF-I levels (Parker et al 1984). The increase in IGF-I is due to GH rather than direct effects of testosterone, since IGF-I is increased by co-administration of GH and testosterone but not by testosterone alone in GH-deficient boys (Parker et al 1984). The influence of testosterone on GH secretion is also illustrated by the ability of exogenous testosterone to correct deficient basal and GHRH-stimulated GH secretion in boys with gonadal dysfunction (Link et al 1986, Mauras et al 1989a.…”
Section: Puberty: Humansmentioning
confidence: 94%
“…Estrogen stimulates the release of GH from the pituitary, thereby increasing serum IGF-I levels. Testosterone also stimulates GH release in the pituitary via its local aromatization to estrogen (Parker et al 1984). However, the sex steroids may also exert a direct GH-independent effect on skeletal growth.…”
Section: Introductionmentioning
confidence: 99%